A co-design approach to examine and develop pathways to open employment for people with acquired brain injury. Issue 1 (6th March 2021) - Bould, Em; Callaway, Libby
Abstract: Background and objectives: People with acquired brain injury (ABI) have traditionally experienced low employment rates, compared with the national average and others with disability in Australia. To positively impact mainstream economic participation following ABI, a co-design approach was used to investigate open employment pathways available and consider necessary pathway features to enable employment for people with ABI. Method: A qualitative focus group methodology was used with four groups: people with ABI; health professionals working with this group; employers providing work for people with ABI and social and injury insurers funding employment services. The project was delivered in two phases: (1) review existing work pathways in Australia and gather knowledge about enablers and barriers to employment following ABI and (2) use ABI lived experience, employers' experience and allied health and social insurer expertise to develop a new pathway to mainstream employment. Results: Co-design helped to identify enablers and barriers to employment of people with ABI, as well as practical strategies to facilitate workplace diversity and inclusion. Enablers included replacing interviews with an onsite assessment to meet key staff and trial work tasks, employer education on ABI, the use of compensatory cognitive aides and graded on-the-job support. This guided the development of a new employment pathway, tailored for people with ABI, called 'Employment CoLab'. Conclusions: The Employment CoLab pathway, when coupled with person-centred collaborative and effective social disability insurance approaches, offers opportunities to build inclusive, sustainable and scalable economic participation and mainstream wages for people with ABI.